(NaRMQNSKOE OB]ESTWENNO(B-(NPOLITI^ESKOE DWIVENIE W (B50 - 60-(NH GODAH (BXIX (NWEKA I rOSSIQ (B/s - d; 9 ((NeREWAN (B:s (NiZD(B-(NWO egu(B,s, 1979)
(NrEZ(B.: (NANGL(B.s
(NbIBLIOGR(B. (NW KONCE GLAW(B.s
(NuKAZ(B. (NGEOGR(B. (NNAZW(B.: (NS(B. 366-373.s
(NuKAZ(B. (NIMEN(B: (NS(B. 374-381.s
Keywords: (NiSTORIQ ARMQNSKOGO NARODAs; (NaRMQNSKOE OB]ESTWENNO(B-(NPOLITI^ESKOE DWIVENIEs -- 50-60-(NE GODY (BXIX (NW(B.s; (NzAPADNYE ARMQNEs -- (N|KONOMIKA I POLITIKAs -- 1830-1860 (NGG(B.s; (NaRMQNSKOE NACIONALXNO(B-(NOSWOBODITELXNOE DWIVENIEs -- 50-60-(NE GG(B. XIX (NW(B.s; (NwOSTO^NAQ aRMENIQ POSLE PRISOEDINENIQ K rOSSIIs; (NrOSSIQ I ARMQNSKIE OB]ESTWENNYE TE^ENIQs -- 50-60-(NE GG(B. XIX (NW(B.s; (NaRMQNO(B-(NRUSSKIE OTNO[ENIQs